Lack of Responsiveness during the Onset and Offset of Sevoflurane Anesthesia Is Associated with Decreased Awake-Alpha Oscillation Power - Pavone, Kara J.; Su, Lijuan; Gao, Lei; Eromo, Ersne; Vazquez, Rafael; Rhee, James; Hobbs, Lauren E.; Ibala, Reine; Demircioglu, Gizem; Purdon, Patrick L.; Brown, Emery N.; Akeju, Oluwaseun (Frontiers in Systems Neuroscience, 2017)
Anesthetic drugs are typically administered to induce altered states of arousal that range from sedation to general anesthesia (GA). Systems neuroscience studies are currently being used to investigate the neural circuit mechanisms of anesthesia-induced altered arousal states. These studies suggest that by disrupting the oscillatory dynamics that are associated with arousal states, anesthesia-induced oscillations are a putative mechanism through which anesthetic drugs produce altered states of arousal. However, an empirical clinical observation is that even at relatively stable anesthetic doses, patients are sometimes intermittently responsive to verbal commands during states of light sedation. During these periods, prominent anesthesia-induced neural oscillations such as slow-delta (0.1-4 Hz) oscillations are notably absent. Neural correlates of intermittent responsiveness during light sedation have been insufficiently investigated. A principled understanding of the neural correlates of intermittent responsiveness may fundamentally advance our understanding of neural dynamics that are essential for maintaining arousal states, and how they are disrupted by anesthetics. Therefore, we performed a high-density (128 channels) electroencephalogram (EEG) study (n = 8) of sevoflurane-induced altered arousal in healthy volunteers. We administered temporally precise behavioral stimuli every 5 seconds to assess responsiveness. Here, we show that loss of eyes-closed, awake-alpha (8-12 Hz) oscillations is associated with lack of responsiveness during sevoflurane effect-onset and -offset. We also show that anteriorization – the transition from occipitally dominant awake-alpha oscillations to frontally dominant anesthesia induced-alpha oscillations – is not a binary phenomenon. Rather, we suggest that periods, which were defined by lack of responsiveness, represent an intermediate brain state. We conclude that awake-alpha oscillation, previously thought to be an idling rhythm, is associated with responsiveness to behavioral stimuli.